Narrativa e acontecimento: como e quando a língua portuguesa se torna pauta em veículos noticiosos do Brasil e Portugal - Rocha, Andréia Maria de Souza (2022)
This research focused on the concept of language that sustains and directs narratives in the media, commencing between two newspapers from Lusophone countries: the Portuguese Diário de Notícias and the Brazilian Correio Braziliense. To enter into the narratives of these materials and analyze how the construction process takes place, in order to perceive the discourse, its nuances of objectivity x subjectivity, besides recognizing which sources are involved and which other voices are present in these narratives or were silenced constituted the process of this research. Amen to this, verifying how the Portuguese language is approached in journalistic articles published in two newspapers of great circulation in their countries can point to a fruitful scenario of studies about the linguistic universe at intersection with the media sphere. The thematic narrative media triad x language x event was the motto for the analysis performed, in order to find convergences and conceptual divergences that stand out within the spaces of intersection in the areas of Linguistics and Social Communication, because the more the language is presented through only the game of right x wrong, based on the grammatical and dicionaristic rules , the more the public will distance themselves from what scientific knowledge has already discovered about the linguistic universe.